Redesigning Small-Scaled Vernacular Lodges in Tunisia: Towards a Renewed Ecolabelling Interpretation - Iman Gawad (Journal of Architecture, Art & Humanistic Science, 2022)
Tunisia has always been concentrating on maximising its tourism growth while protecting its natural and cultural environments. Despite of various perceived limitations, Ecotourism has therefore become a viable dimension of tourism in many touristic areas in the country. The heritage sites in the southern part of Tunisia, are known to host a large number of Mid and Small-scaled Ecolodges. However, the redesign of these lodges appears to be a difficult task for architects, and some are undoubtedly stronger than others in their contribution to Ecotourism. The use of International Ecolabels in this regard, ensures that a tourism project is sustainable, while enhancing the ecological efficiency and competitiveness of the tourism industry in the area. The requirements for these Ecolabels must be complemented by goals designed to be suitable for the natural and cultural local aspects. Although in principle, and mostly in practice, Ecolabels are considered as effective tools in the design and management of touristic projects, they still face some challenges. The problem in Tunisia is that most of the Ecolodges’ architectural design misinterprets the environmentally and socially sustainable practices that would get them closer to the “International Recognised Ecolabel Certifications” but continue to identify themselves as such, often for marketing purposes. A comparative analysis is presented in this paper to explain the variations in the usage of several forms of Ecolabeling and accreditation systems and their effect on sustainability when implemented. It also assesses an example of Ecolodges in “Chenini” village, “Tatouine” region, south of Tunisia, and proposes strategies to turn it into more of an authentic Ecolodge in the future towards an Ecolabelling certification that is internationally recognized.